New developments in the representation of Saharan dust sources in the aerosol-climate model ECHAM6-HAM2 - Heinold, Bernd; Tegen, Ina; Schepanski, Kerstin; Banks, Jamie R. (München : European Geopyhsical Union, 2016)
In the aerosol-climate model ECHAM6-HAM2, dust source activation (DSA) observations from Meteosat Second Generation (MSG) satellite are proposed to replace the original source area parameterization over the Sahara Desert. The new setup is tested in nudged simulations for the period 2007 to 2008. The evaluation is based on comparisons to dust emission events inferred from MSG dust index imagery, Aerosol Robotic Network (AERONET) sun photometer observations, and satellite retrievals of aerosol optical thickness (AOT). The model results agree well with AERONET measurements especially in terms of seasonal variability, and a good spatial correlation was found between model results and MSG-SEVIRI (Spinning-Enhanced Visible and InfraRed Imager) dust AOT as well as Multi-angle Imaging SpectroRadiometer (MISR) AOT. ECHAM6-HAM2 computes a more realistic geographical distribution and up to 20 % higher annual Saharan dust emissions, using the MSG-based source map. The representation of dust AOT is partly improved in the southern Sahara and Sahel. In addition, the spatial variability is increased towards a better agreement with observations depending on the season. Thus, using the MSG DSA map can help to circumvent the issue of uncertain soil input parameters. An important issue remains the need to improve the model representation of moist convection and stable nighttime conditions. Compared to sub-daily DSA information from MSG-SEVIRI and results from a regional model, ECHAM6-HAM2 notably underestimates the important fraction of morning dust events by the breakdown of the nocturnal low-level jet, while a major contribution is from afternoon-to-evening emissions. publishedVersion